Hemoglobin profiles of siblings of thalassemia patients - Muhammad Riza; Septin Widiretnani (Paediatrica Indonesiana, 2015)
Background Thalassemia and hemoglobinopathies are themost common inherited disorders in many areas of the world,including South East Asia. The siblings of thalassemia major is agroup of high risk to carry the gene of thalassemia. Determiningthe carrier is useful for early treatment planning and preventionto the next child.Objective To determine carrier status among siblings ofthalassemia patients using a capillary electrophoresis system.Methods A cross-sectional study on the siblings of thalassemiamajor patients was performed from January 2011 to February2012 at Dr. Moewardi Hospital. Complete blood counts wereperformed in the siblings. Subjects with mean corpuscular volume(MCV) <80 fl and mean corpuscular hemoglobin (MCH) <27pg were subjected to analize hemoglobin fraction by capillaryelectrophoresis.Results Of the 26 subjects, there were 12 males and 14 females.The mean age was 9.38 (SD 6.8) years (range 1 to 29 years). Fromthe siblings, 10 were identified as normal, 5 were identified as ßthalassemia carriers and 5 were hemoglobin E (HbE) carriers. Sixsiblings were diagnosed with ß thalassemia/ HbE.Conclusion There are high occurrence of the two common typesof thalassemia carriers (ß and HbE) in our small group of subjectswho had a family history of thalassemia. Most of the siblingsof thalassemia had low MCV and MCH.